2011
DOI: 10.1007/s10447-011-9116-6
|View full text |Cite
|
Sign up to set email alerts
|

Attending to Diversity Representation Among Council for Accreditation of Counseling and Related Educational Programs (CACREP) Master’s Programs: A Pilot Study

Abstract: Extant research has neglected to explore the diversity representation of counselor education programs. This pilot study sought to examine the extent to which CACREPaccredited master's-level programs attend to the representation of people of color, individuals with dis/abilities, lesbian, gay, bisexual (LGB), and transgender persons within admissions, enrollment, and graduation data. The findings indicated little consistency in the maintenance of students' demographic characteristics among participating program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Counselor educators impact the development of counselor identity, yet there is a dearth of literature on integrating advocacy into counseling courses to meet the criteria of advocacy as part of a counselor's professional identity (Reiner et al, 2013;Shin, Smith, Goodrich, & LaRose, 2011). This article addresses the need for "clearer structure, guidance, and support" for social justice advocacy in counseling and specifically counselor education (Toporek et al, 2009, p. 266).…”
Section: Application To Counselor Education Through Cacrep Standardsmentioning
confidence: 99%
“…Counselor educators impact the development of counselor identity, yet there is a dearth of literature on integrating advocacy into counseling courses to meet the criteria of advocacy as part of a counselor's professional identity (Reiner et al, 2013;Shin, Smith, Goodrich, & LaRose, 2011). This article addresses the need for "clearer structure, guidance, and support" for social justice advocacy in counseling and specifically counselor education (Toporek et al, 2009, p. 266).…”
Section: Application To Counselor Education Through Cacrep Standardsmentioning
confidence: 99%
“…This suggests that programs have opportunities to reduce student resistances through examination of these areas. Graduate programs can promote student multicultural competence development through recruitment and retention of students and faculty of color, inclusion of multicultural course work, providing opportunities to counsel culturally diverse clients, regularly evaluating student competence development, having physical spaces that reflect diverse cultural aesthetics, and having faculty engaged in multicultural research (e.g., Baker et al, 2015; Dickson & Shumway, 2011; Shin, Smith, Goodrich, & LaRosa, 2011). Surprisingly, students in this study—including those who did identify having a resistance—believed that their multicultural training environment moderately addressed cultural issues.…”
Section: Discussionmentioning
confidence: 99%
“…Counselor educators can conduct a comprehensive program assessment to identify training aspects restrictive to student cultural development. Educators can assess their programs’ conceptualization and operationalization of multicultural training (Dickson & Shumway, 2011), level of attention to cultural safety for students (Hinojosa & Carney, 2016), and recruitment and retention of diverse students and faculty (Shin et al, 2011). Educators can include student and alumni perspectives in their assessment to understand constituent training experiences and resistances.…”
Section: Discussionmentioning
confidence: 99%
“…Participants identified as female ( n = 138, 85.7%), male ( n = 22, 13.7%), and transgender ( n = 1, 0.6%). Although there are no currently published articles addressing the racial and cultural demographics of CACREP‐accredited programs in the United States, Shin, Smith, Goodrich, and LaRosa () suggested that racially and culturally diverse groups are underrepresented in counselor education. The demographics of the current sample corresponds with the trends noted in Shin et al's review of four recently published articles that reported demographics of participants in CACREP‐accredited programs.…”
Section: Methodsmentioning
confidence: 99%